Pelatihan Pembuatan Desain Busana Secara Digital Bagi Peserta Didik SMK Tata Busana di Yogyakarta - Himmah, Laila Nurul; Mahanani, Chytra; Elvera, Resi Sepsilia (Abdi Seni, 2023)
This training activity aims to provide knowledge and skills in making digital fashion designs as a continuation of the process of making manual fashion designs for students of SMK Fashion Yogyakarta. The target of the activity is the third-year students of SMK (vocational high school) of the Fashion Expertise Program in Yogyakarta. The lecturers doing off-campus project activities related to fashion design provide training on making fashion designs digitally with the CLO 3D application. In the form of training, the speaker not only delivers material or theory but also conducts training directly to students. This activity is divided into three stages: the preparation stage, the implementation stage, and the evaluation stage. The methods used in this training activity are lectures to convey fashion design theory, demonstration methods to provide examples of the process of making fashion designs digitally, and the practice of making fashion designs using the CLO 3D application carried out by students accompanied by a presenters team. The activity results are (1) Implementing practical activities to make fashion designs with digital techniques attended by three classes, XII Busana 1, 2, and 3, consisting of 90 students. (2) Students are trained in making fashion designs with digital techniques using the CLO 3D application. Based on the evaluation of digitally making fashion designs, participants' attendance during the training reached 96%. While based on student practice results, 62% of student design result is categorized as 'good,' while 38% means fairly good.